Are there differences in HIV retention in care between female and male patients in Indonesia? A multi-state analysis of a retrospective cohort study. - Annisa Rahmalia; Michael Holton Price; Yovita Hartantri; Bachti Alisjahbana; Rudi Wisaksana; Reinout van Crevel; Andre J A M van der Ven (PLoS ONE, 2019)
Background Little is known about HIV treatment outcomes in Indonesia, which has one of the most rapidly growing HIV epidemics worldwide. Methods We examined possible differences in loss to follow-up (LTFU) and survival between HIV-infected females and males over a 7-year period in an HIV clinic in Bandung, West Java. Data imputation was performed on missing covariates and a multi-state Cox regression was used to investigate the effects of sex and other covariates on patient transitions among four states: (1) clinic enrollment with HIV, (2) initiation/continuation/re-initiation of antiretroviral therapy (ART), (3) LTFU, and (4) death. Results We followed 3215 patients (33% females), for a total of 8430 person-years. ART was used by 59% of patients at some point. One-year retention was 73% for females and 77% for males (p = 0.06). One-year survival was 98% for both females and males (p = 0.15). Females experienced a higher relative hazard to transition from HIV to LTFU (adjusted hazard ratio 1.21; 95% confidence interval 1.00-1.45), but this decreased after adjustments for clinical variables (aHR 0.94; 95% CI 0.79-1.11). Similarly, a lower relative hazard in females to transition from ART to death (aHR 0.59; 95% CI 0.35-0.99) decreased after adjustments for demographic variables. Conclusion This Indonesian cohort has low ART uptake and poor overall pre- and post-ART retention. Female-male differences in survival and retention were gone after adjusting for clinical and sociodemographic factors such as CD4 count and education level. Efforts should be made to improve retention among patients with lower education.